A solar powered portable potentiostat for environmental monitoring - Matthew McCole; Martin Bradley; Margaret McCaul; Denis McCrudden (Results in Engineering)
This study presents the design and development of a novel low-cost portable electrochemical system for rapid accurate detection of nitrate in soil pore water. The portability of the system addresses the need for on-site analysis which facilitates immediate decision-making for farmers, environmental researchers, and others. Using the Infineon CY8CKIT-059 and IoT technology enabled remote data acquisition and transmission allowing more frequent and continuous monitoring than traditional methods. The developed system is therefore advantageous in reducing excessive nitrate fertiliser application, consequently minimising their effects on environmental and health related issues. The system utilised 3D printing technology to create electrodes that after activation and modification could detect nitrate and nitrite ions using differential pulse voltammetry. The system was developed for less than €60 and was comparable to a commercially available metrohm potentiostat. The developed 3D printed electrodes were calculated to have LOD’s of 13.94 µM for nitrite and 66.99 µM for nitrate. Nitrate levels were accurately detected in soil pore water samples and nitrite levels were also accurately recovered from spiked samples with a mean accuracy of 106.33 % and 94.82 % respectively. This work showcases the potential for scalable production and widespread adoption of this technology for sustainable soil management practices.